Outcome of extended right lobe liver transplantations - Lozanovski, Vladimir J.; Unterrainer, Christian; Döhler, Bernd; Süsal, Caner; Mehrabi, Arianeb (Liver transplantation, 2022)
Split‐liver transplantation offers a solution to the organ shortage problem. However, the outcomes of extended right lobe liver transplantation (ERLT) and whether it is a suitable alternative to full‐size liver transplantation (FSLT) remain controversial. We compared the outcomes of ERLT and FSLT in adult recipients of 43,409 first deceased donor liver transplantations using Cox regression. We also analyzed 612 ERLT and 1224 FSLT 1:2 matched cases to identify factors that affect ERLT outcome. The risk of graft loss was significantly higher following ERLT than following FSLT during the first posttransplantation year in the matched and unmatched collective (hazard ratio [HR], 1.39 and 1.27 and P = 0.01 and 0.006, respectively). Every additional hour of cold ischemia time (CIT) increased the risk of 1‐year graft loss by 10% in the ERLT group compared with only 3% in the FSLT group (P = 0.003 and <0.001, respectively). Importantly, the outcome of ERLT and FSLT did not differ significantly if the CIT was below 10 hours (HR, 0.71; P = 0.22). One‐year graft and patient survival were lower in high‐risk ERLT recipients with a Model for End‐Stage Liver Disease (MELD) score of ≥20 (HR, 1.88; P = 0.03 and HR, 2.03; P = 0.02). In the male recipient-male donor combination, ERLT recipients had a higher risk of 1‐year graft loss than FSLT recipients (HR, 2.44; P = 0.006). This was probably because of the significantly higher MELD score in ERLT recipients (P = 0.004). ERLT in adults is an adequate alternative to FSLT and offers an elegant solution to the problem of organ shortage as long as the cold storage is less than 10 hours and the recipient’s MELD score is <20.